Essentials of psychiatric mental health nursing : a communication approach to evidence-based care - Varcarolis, Elizabeth M. (New York: Elsevier, 2017)
"Get a full understanding of today's psychiatric nursing practice in less time! Essentials of Psychiatric Mental Health Nursing, 3rd Edition offers the perfect balance of essential nursing interventions and clinical content paired with current research and evidence-based practice to fully equip you for today's field of mental health nursing. This new edition continues to retain the reader-friendly style, emphasis on therapeutic communication, and the nursing process organization that was successful in the previous edition. It also includes additional DSM-5 disorders, illustrations of various neurobiology disorders, a new neurobiology learning tool, and new NCLEX review questions to help you pass your course and thoroughly prepare for the psychiatric nursing section of the NCLEX."--
Unit I: Essential Theoretical Concepts for Practice. Practicing the Science and the Art of Psychiatric Nursing -- Mental Health and Mental Illness -- Theories and Therapies -- Biological Basis for Understanding Psychopharmacology -- Settings for Psychiatric Care -- Legal and Ethical Basis for Practice -- Unit II: Tools for Practice of the Art. Nursing Process and QSEN: The Foundation for Safe and Effective Care -- Communication Skills: Medium for All Nursing Practice -- Therapeutic Relationships and the Clinical Interview -- Unit III: Caring for Patients with Psychobiological Disorders. Trauma and Stress-Related Disorders -- Anxiety, Anxiety Disorders, and Obsessive-Compulsive Disorders -- Somatic Symptom Disorders and Related Disorders -- Personality Disorders -- Eating Disorders -- Mood Disorders: Depression -- Bipolar Spectrum Disorders -- Schizophrenia Spectrum Disorders and Other Psychotic Disorders -- Neurocognitive Disorders -- Substance-Related and Addictive Disorders -- Unit IV: Caring for Patients Experiencing Psychiatric Emergencies. Crisis and Mass Disaster -- Child, Partner, and Elder Violence -- Sexual Violence -- Suicidal Thoughts and Behaviors -- Anger, Aggression, and Violence -- Care for the Dying and Those Who Grieve -- Unit V: Age-Related Mental Health Disorders. Children and Adolescents -- Adults -- Older Adults -- Appendixes A. DSM-5 -- Classification B. NANDA-Approved Nursing Diagnoses.
Includes bibliographical references and index.
Keywords: Psychiatric nursing; Mental Disorders -- nursing; Psychiatric Nursing -- methods; Evidence-Based Nursing